Shortening duration of untreated illness in young people with first episode eating disorders: protocol of a randomised controlled feasibility trial of a smartphone friendly multi-modal decision-making tool (FREED-M) to improve help-seeking - Luiza Grycuk; Dina Monssen; Molly R. Davies; Helen Sharpe; Karina L. Allen; Vibhore Prasad; Rachel Potterton; Priya Popat; Victoria A. Mountford; Sheryllin McNeil; Vanessa Lawrence; Nina Grant; et al. (Pilot and Feasibility Studies)
Abstract Background Early intervention gives young people the best chance to recover from eating disorders (EDs). An important focus of early intervention is shortening the time between a person first developing symptoms and starting treatment (duration of untreated eating disorder; DUED). Patient-related factors (e.g. poor mental health literacy and help-seeking difficulties) are strongly associated with DUED. The aims of our study are to co-design and test the feasibility of FREED-Mobile (FREED-M), an online intervention tool for young people with early-stage EDs. This tool aims to improve knowledge about EDs, increase motivation to seek treatment and teach early steps towards change or recovery, thus reducing DUED. Methods We will carry out a randomised controlled feasibility trial comparing the FREED-M tool with a control intervention where individuals are sign-posted to an ED charity website. The objectives of the proposed trial are to establish/estimate: (a) attrition rates at follow-up (primary feasibility outcome); (b) participant recruitment; (c) intervention uptake, completion rates and acceptability; (d) intervention effect sizes and standard deviations for outcomes to inform the sample size calculation for a large-scale randomised controlled trial (RCT); (e) stakeholder views on the intervention. We aim to recruit 116 participants (young people, aged 16–25, with first episode ED) from primary care, schools and universities, ED services and social media. Online assessments will be carried out at baseline, end of intervention and follow-up (weeks 0, 4 and 12 post-randomisation, respectively). Outcomes will include motivation and readiness to change, attitudes and intentions towards help-seeking, ED symptoms, mood and social functioning, and health-related quality of life. Additionally, we will carry out a qualitative evaluation of participants’ views of the intervention and study design. Discussion The results of this feasibility trial will inform adaptations to the intervention as needed, as well as the study design (e.g. sample size, primary outcomes) of a future large-scale RCT to assess the effectiveness of the FREED-M intervention. If effective, this novel, online intervention has the potential for wide dissemination and for substantially reducing DUED to improve long-term patient outcomes. Trial registration ISRCTN, ISRCTN15662055. Registered 27 July 2022, https://www.isrctn.com/ISRCTN15662055 .